Experimental study for asphalt laying using control of pavement compaction technology on roads - Bertulienė, Lina; Augutis, Aurimas (International Conference “Environmental Engineering”, 2017)
Hot mix asphalt (HMA) is produced and laid at high temperature and therefore it is subjected to segregation due to differential cooling, which usually occurs during asphalt material transportation and road pavement construction. If mixing temperature is inconstant the degree of compaction may vary, and this will inevitably result in poor performance of the newly laid road pavement. This study describes factors influencing the quality of asphalt pavement construction and analyses results of repair of the selected road section using the solutions of the asphalt mix compaction control technology with the aim to increase the service life of road pavement and to reduce construction costs. Data were obtained by the asphalt pavement compaction control system TOPCON C 3A built in the HAMM company rollers HD 75 and HD 20 used at the paving site, and by the TROXLER 3451 device used for the self-control density measuring tests. The data obtained enabled to determine the number of rolling passes, temperature differentials of asphalt pavement and pavement compaction.